Analisis Akad Wadi'ah pada Produk Tabungan Pendidikan di KSPPS Matholi’ul Anwar Karanggeneng Lamongan - Dwi Aprilianto; Nicky Utami Novitasari (Universitas Islam Lamongan, 2023)
This research was motivated by the existence of educational savings deposits at KSPPS Matholi'ul Anwar Simo Sungelebak, Karanggeneng District, Lamongan Regency with a wadi'ah contract. The formulation of the problem in this study is how to implement wadi'ah contracts on educational savings products at KSPPS Matholi'ul Anwar, Karanggeneng District, Lamongan Regency and how to analyze the implementation of wadi'ah contracts on educational savings products at KSPPS Matholi'ul Anwar, Karanggeneng District, Lamongan Regency. The purpose of this study is to find out how the implementation of wadi'ah contracts on educational savings products and how to analyze the implementation of wadi'ah contracts on educational savings products at KSPPS Matholi'ul Anwar, Karanggeneng District, Lamongan Regency. This research uses a qualitative research type. The results of this study show that from the results regarding the implementation of wadi'ah contracts on educational savings at KSPPS Matholi'ul Anwar simo sungelebak Karanggeneng sub-district, Lamongan Regency, the savings products are in accordance with sharia principles which are clarified with the terms and pillars fulfilled and KSPPS Matholi'ul Anwar has given bonuses to customers but the cooperative has never given bonuses again.